Relationship Among Reference Evapotranspiration Models for Add Region of Rajasthan - Goyal, R K; Gupta, V P (Annals of Arid Zone, 2016)
There are many methods for estimation of reference evapotranspiration (ET 0)’ These methods have been developed for specific sites. and need to be tested for other regions before their application. Several researchers have compared the results obtained from ditferent evapotranspiration methods. However, no single existing method is universally applicable under all climatic conditions. Application of many of these methods is restricted because of large amount of data required. There has always been a need to estimate ET using limited meteorological data, whatsoever is available. Keeping in view the above difficulty. a study was undertaken to develop interrelationships among frequently used models for estimation of reference ET. Several standard models, namely Blaney-Criddle. Radiation, modified Penman and most recently developed Penman-Monteith and others have been used to develop interrelationships. About 30 years of weekly meteorological data of Jodhpur (Rajasthan) have been used to develop the interrelationships. Such interrelationships could be used as an additional tool to convert ETo estimated by one method to another method. Interrelationships between different models of ET" are also useful for comparing the performance of different models. The present paper provides an opportunity to select a method of using limited available data under arid zone conditions.